The economic and strategic motives for antidumping filings - Prusa, Thomas J.; Skeath, Susan; National Bureau of Economic Research (Cambridge National Bureau of Economic Research, 2001)
This paper takes a critical look at the trends in worldwide antidumping (AD) case filings during the last two decades. We examine the motives for AD filings by countries in an attempt to identify whether economic or strategic concerns are driving the recent upsurge in AD use. We begin by providing a comprehensive overview of the data on cases initiated in the 1980 to 1998 period. We then use non-parametric methods to identify national motivations for the use of antidumping. Results show considerable support for the importance of strategic concerns in driving AD case filings. This suggests that the rise in AD activity cannot be solely explained by an increase in unfair trading practices.
Keywords: Antidumping duties; Competition, Unfair; Dumping (International trade) -- Law and legislation